PENGARUH LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN DAN EARNING MANAGEMENT TERHADAP NILAI PERUSAHAAN (Studi empiris pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2013-2016) - Amiyatun, 14.05.52.0117; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2018)
The value of the firm is the performance of company that isreflected by the price of shares in the form of demand and supply the capital market reflects publicâs assessment of the companyâs performance. Corporateâs value is influenced by several factors including the leverage, profitability, company size and earning menejemen. This research aimed to examine the effect of leverage, profitability, company size and earning menejemen on compeny value on manufacturing compenies listed in indonesia capital exchange year 2013-2016. The result of this research simultaneously leverage,profitability, compeny size, and earning menejemen influence on value of compeny. While partially show that leverage and earning menejemen significant negative effect on value compeny value, meanwhile profitability and compeny size significant positive effect on compeny valueKeyword: leverage, profitability, company size, earning management and compeny value